Spectroscopic probing of ortho-nitrophenol localization - Sanchez, Julieta Maria (2007)
In the present study we estimated the localization of ortho-nitrophenol (ONP) within model membranes through its efficiency to quench and to modify the anisotropy of DPH and TMA-DPH fluorescence. These fluorescent probes are known to sense the hydrocarbon core and the polar head group region of membranes, respectively. TMA-DPH fluorescence in MLVs was more efficiently quenched than DPH (Kq,TMA-DPH = 2.36 and Kq,DPH = 1.07 mM ns-1). Moreover, these results demonstrated the interfacial localization of ONP and may contribute to understand membrane-mediated mechanisms of ONP-induced toxicity and the behavior of ONP as a product of several enzymatic reactions occurring in the presence of lipid-water interfaces.